DEVELOPMENT OF EFFICIENT CHAIN TRANSMISSION CONSTRUCTION BASED ON ANALYSIS OF CONSTRUCTIVE CHARACTERISTICS OF CHAIN DRIVES OF TECHNOLOGICAL MACHINES - Aliyev, Elmurod; Mamaxonov, A’zam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In the article, the constructions of roller chain transmissions with a new composition, which work smoothly, have high durability, and have a longer service life, are developed for the drives of technological machines for the production of oil from plants. It is proposed to use the proposed extension structures in the handling of the seed distribution drum in the hopper.